Walid Khalidi: The Historian Who Turned Palestinian Memory into a Human Right (Countercurrents, 2026)
Walid Khalidi devoted his century-long life to a simple but radical principle: that the memory of a people is a human right, and that documenting their erasure is an act of historical justice.
Palestine